Malaria prevention measures in Burkina Faso: distribution and households expenditures - Yaya Bocoum, Fadima (Int J Equity Health, 2014)
BACKGROUND: The provision of insecticide-treated nets (ITNs) is widely accepted in Burkina Faso thanks to large-scale national distribution campaigns. However, household also use other methods of prevention. Thus far, there is little knowledge about the expenditures of these malaria prevention methods, particularly in combination with the national interventions. This paper presents the utilization levels and expenditures of malaria prevention tools in Burkina Faso and explores the potential inequality in ownership. METHODS: The analysis is based on a cross-sectional survey, conducted during the 2010 high transmission season from July to September in the Nanoro Health and Demographic Surveillance Site. Following a systematic sampling technique, the survey covers 500 households with children under 5 years of age from 24 villages. In the survey, households were asked about expenditures on malaria prevention methods in the month preceding the survey. This includes expenditure on coils, indoor spraying, aerosols, repellents, herbs, cleaning of the environment and clearing of the vegetation. The data analysis was conducted with SPSS taking into account the socio-economic status (SES) of the household to examine any differences in the utilization of the prevention method and expenditure quintiles. An asset-based index, created through principal components analysis (PCA), was used to categorize the households into quintiles. FINDINGS: Of the households surveyed, 45% used one preventive measure in the past month; 29% used two measures; and 25% used three or more measures. A significant association was found between the number of prevention measures and the SES of the household (p < 0.05). The majority of households owned at least one insecticide treated net (ITN) (98%). Among households that used ITN, 53.8% used methods other than bed nets. The majority of households paid nothing for malaria prevention. CONCLUSION: Most of the households received bed nets and other preventive method for free. There is equity in expenditures across SES groups. Free distribution of ITNs ensured that there was equity in ITN ownership among households. More research on the possibility of increasing access to other locally relevant methods of malaria control that proved to be effective is need.